Strategies for Preventing Bankruptcy: Adopting Insolvency Tests from the United States Perspective to Indonesia - Kendry Tan; Yudhi Priyo Amboro; Elza Syarief (Journal of Judicial Review, 2023)
Companies don't always make a profit and taking loans from banks or other companies to ensure smooth business operations can put a company's existence in danger. Failure to repay loans can lead to bankruptcy, declared by the competent commercial court upon request of the creditor or debtor. The ease with which bankruptcy requirements are regulated under Indonesian law can lead to economic problems. This study seeks to examine the differences between bankruptcy laws in Indonesia and the United States, the challenges in implementing an insolvency test in Indonesia, and the benefits of such a test. The research method used is normative-juridical, employing a conceptual and statutory approach to assess the benefits and obstacles of implementing insolvency tests in Indonesia. The findings suggest that applying insolvency tests can have a positive impact on economic growth, including reducing the number of bankrupt companies and decreasing unemployment, which contributes to development. As a result, it's necessary to modify Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations to enable the use of insolvency tests in bankruptcy applications in Indonesia.